Haida boys near totem poles, canoes and houses at Howkan village, Long Island, Alaska, ca. 1897 - Winter, Lloyd Pond, E. Percy
Boys pose in front of canoes (and fishing nets), houses and many totem poles. The village houses a subtribe of the Haida called the Kaijani. Caption on image: Totems at Howkan Village. Copyright by Winter & Pond Co. Information from Winter & Pond Company's The totems of Alaska, 1909, leaf 1